Meta-analysis of clopidogrel pretreatment in acute coronary syndrome patients undergoing invasive strategy. (15th February 2017) - Nairooz, Ramez; Valgimigli, Marco; Rochlani, Yogita; Pothineni, Naga Venkata; Raina, Sameer; Sardar, Partha; Mukherjee, Debabrata; Naidu, Srihari S; Shavelle, David M.
Abstract: Background: It is unknown whether pretreatment with clopidogrel in acute coronary syndrome (ACS) managed invasively, is superior to a strategy of administering clopidogrel in the cardiac catheterization laboratory at the time of percutaneous coronary intervention (PCI). Current practice guidelines do not endorse one strategy over the other. Methods: A comprehensive literature search was done to identify all relevant studies comparing pretreatment with clopidogrel to administration in the cardiac catheterization laboratory at the time of PCI (no pretreatment). A meta-analysis using a random effects model was used to calculate outcomes of interest. Results: Our search identified 16 studies including 61, 517 ACS patients undergoing cardiac catheterization. At 30 days, clopidogrel pretreatment was associated with lower MACE 7.67% vs 9.46% (odds ratio (OR) 0.77, 95% confidence interval (CI) [0.68, 0.86]; P  < 0.0001) and all-cause mortality 2.8% vs 4.1% (OR 0.70, 95% CI [0.58, 0.85]; P  = 0.0003). Mortality according to the longest follow up available was also significantly lower with pretreatment. No difference in major bleeding events was observed. These results were not significantly different between randomized vs observational studies or STEMI vs NSTEACS patients. Sensitivity analysis showed significantly lower MACE 7.98% vs 9.6% (OR 0.83, 95% CI [0.71, 0.96]; P  = 0.01) without increased major bleeding in NSTEACS patients undergoing PCI within 48 h from pretreatment. Conclusion: In ACS patients undergoing PCI, clopidogrel pretreatment was associated with significantly lower 30 day all-cause mortality and major adverse cardiovascular events without increased major bleeding events.